Self-Management pada Anak Epilepsi Menggunakan Mobile Health Application: Literature Review - Putri Nila Sari; Indah Putri Irdelia (STIKes Payung Negeri Pekanbaru, 2021)
Background: The most common chronic neurologic among pediatric is epilepsy. So we need a technology that can be used for epilepsy self-treatment. One of technology that can be used is a mobile health application for self-management. Purpose: to describe mobile health application for self-management in children with epilepsy. Methods: This study was used a literature review method from an online database UI: Scopus, EBSCOhost, ProQuest, and Science Direct (2016-2020) using the keywords mobile application, mobile health, self-management, Epilepsy. Results: The search results showed there are 10 articless were selected and to be reviewed and it was found that mobile health application can be used for self-management in children with epilepsy, and also increasing medication adherence, and improves seizure control. Conclusion: Mobile health application provides benefits for children with epilepsy to do self-management.